Analisis Tingkat Kepuasan Pengguna Sistem Informasi Kerja Praktek dan Skripsi (SKKP) Menggunakan Metode End User Computing Satisfaction (EUCS) - Nanny Raras Setyoningrum (Journal of Applied Informatics and Computing, 2020)
The advantages of information technology in the education has developed a lot, especially in universities. An example of the application of tertiary level information technology is the delivery of information presented through the university's official website. One of the web-based systems owned by the STTI Tanjungpinang is the Sistem Informasi Kerja Praktek dan Skripsi (SKKP). With this technology, the process of submitting titles to the registration of practical work trials and student theses has been switched online. Analysis of the level of satisfaction is important to know the extent of expectations and perceptions of system users in an effort to achieve the perfection of an information system and can meet user expectations. One method in analyzing user satisfaction levels is end user computing satisfaction (EUCS). Dimensions in EUCS consist of content, accuracy, format, ease of use and timeliness. This type of research is descriptive research that is intended to describe the phenomena that exist, which took place at this time or in the past. Data collection methods included observation, interviews and distribution of questionnaires with a sample of 35 respondents who were active SKKP users. The results of the analysis of user satisfaction level SKKP STTI Tanjungpinang using the EUCS method of 78.69% with a gap of 21.31% means users are in the range of satisfied categories. From the five dimensions, the variable content has the smallest gap of 8.69% while the largest gap is in the accuracy variable, which is 32.02%.